Debris flows dynamic risk assessment and interpretable Shapley method-based driving mechanisms exploring – A case study of the upper reach of the Min River - Yufeng He; Mingtao Ding; Yu Duan; Hao Zheng; Wen He; Jun Liu (Ecological Indicators)
Debris flow is one of the most devastating natural hazards. Identifying the dynamic changes and driving factors of debris flow risk can enhance hazard mitigation and prevention. It is not clear what factors can mostly lead to debris flow risk change in mountainous areas, particularly some of these areas in the context of intense earthquakes, rapid urbanization, and climate change. To address these questions, an ensemble learning model was constructed to estimate the debris flow risk of the baseline period (2000) and the current period (2020) in the upper reach of the Min River. The study found that the areas with extremely high debris flow risk decreased by 18.57%, while the areas with moderate and high risk levels increased by 8% and 14% respectively. With this trend of overall risk increasing, the population and buildings affected by extremely high debris flow risk have increased by 20% and 30% respectively. Based on the interpretable learning model of SHAP (The Shapley Additive Explanations value), the mechanisms by driven factors that lead to changes in risk were explored. Population, elevation and NDVI are the most influential factors leading to changes in risk. Specifically, the increase in risk in the low elevation area is due to the rapid urbanization caused by the increase of population and GDP. While the risk change in higher elevation areas contributes to the variation of vegetation and precipitation. These findings have implications for debris flow mitigation and contribute to the understanding of the multiple factors that impact debris flow risk.